Learning assessment techniques : a handbook for college faculty - Barkley, Elizabeth F. (Jossey-Bass, 2016)
"50 Techniques for Engaging Students and Assessing Learning in College Courses Do you want to: Know what and how well your students are learning? Promote active learning in ways that readily integrate assessment? Gather information that can help make grading more systematic and streamlined? Efficiently collect solid learning outcomes data for institutional assessment? Provide evidence of your teaching effectiveness for promotion and tenure review? Learning Assessment Techniques provides 50 easy-to-implement active learning techniques that gauge student learning across academic disciplines and learning environments. Using Fink's Taxonomy of Significant Learning as its organizational framework, it embeds assessment within active learning activities. Each technique features: purpose and use, key learning goals, step-by-step implementation, online adaptation, analysis and reporting, concrete examples in both on-site and online environments, and key references--all in an easy-to-follow format. The book includes an all-new Learning Goals Inventory, as well as more than 35 customizable assessment rubrics, to help teachers determine significant learning goals and appropriate techniques. This book also provides access to a downloadable worksheet to guide teachers through the seven steps of the Learning Assessment Techniques planning and implementation cycle. College teachers today are under increased pressure to teach effectively and provide evidence of what, and how well, students are learning. An invaluable asset for college teachers of any subject, Learning Assessment Techniques provides a practical framework for seamlessly integrating teaching, learning, and assessment"--